PSYCHIATRIC MORBIDITY AND SUBSTANCE ABUSE AMONG MALE JUVENILE OFFENDERS IN BANGLADESH - Maruf, Mohammad Muntasir; Rahman, Farzana; Khan, Muhammad Zillur Rahman; Jahan, Nasim (LIFE: International Journal of Health and Life-Sciences, 2015)
Juvenile offenders are generally vulnerable to psychiatric illness. The objectives of the study were to determine the types of psychiatric disorders among male juvenile offenders in Bangladesh and to find out their socio-demographic correlation and relation with substance abuse. This was a cross-sectional study conducted in Juvenile Development Center (Boys’), Bangladesh. All the male offenders of 9-18 years were included in the study during January - June 2011. Total respondents were 138. Validated Bangla version of the Development and Well-Being Assessment (DAWBA) was used to determine psychiatric disorders which were assigned based on ICD-10 diagnostic criteria. Information regarding socio-demography and substance abuse were collected through face-to-face interview using a semi-structured questionnaire and from the case-notes. Data analysis was done by SPSS for windows 15 version. The mean (±SD) age of the respondents was 14.2 (±1.7) years. Psychiatric disorders were diagnosed in 57.2% of the respondents. The rate of emotional disorders (48.1%) was higher than behavioral disorders (38.4%). Regarding specific disorders, conduct disorder (46.8%)and major depressive disorder (43.0%) were the most common diagnoses. Statistically significant association of psychiatric disorders was found with the urban background (57.6%), primary level of education (63.5%), and employment (75.5%). Among the respondents, 38.4% had a history of substance abuse. Among the substance abusers, 77.4% had psychiatric disorders. It can be concluded that there was the considerable rate of psychiatric disorders and substance abuse among male juvenile offenders in the development center. Broad-based replication study could confirm these findings.